2021
DOI: 10.3390/mi12101151
|View full text |Cite
|
Sign up to set email alerts
|

A Portable Device for LAMP Based Detection of SARS-CoV-2

Abstract: This paper reports the design, development, and testing of a novel, yet simple and low-cost portable device for the rapid detection of SARS-CoV-2. The device performs loop mediated isothermal amplification (LAMP) and provides visually distinguishable images of the fluorescence emitted from the samples. The device utilises an aluminium block embedded with a cartridge heater for isothermal heating of the sample and a single-board computer and camera for fluorescence detection. The device demonstrates promising r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Isothermal amplification techniques range in terms of total quantity of primers and enzymes employed, the temperature at which the amplification takes place, and the sorts of templates used. Table 2 [75][76][77][78][79][80][81][82][83][84][85][86][87] summarizes the several isothermal amplification platforms established for detecting SARS-CoV-2 in both laboratory and clinical samples.…”
Section: Isothermal Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Isothermal amplification techniques range in terms of total quantity of primers and enzymes employed, the temperature at which the amplification takes place, and the sorts of templates used. Table 2 [75][76][77][78][79][80][81][82][83][84][85][86][87] summarizes the several isothermal amplification platforms established for detecting SARS-CoV-2 in both laboratory and clinical samples.…”
Section: Isothermal Amplificationmentioning
confidence: 99%
“…Summary of the several isothermal amplification platforms established for SARS-CoV-2 diagnostics in both laboratory and clinical samples [Refs [75][76][77][78][79][80][81][82][83][84][85][86][87]. …”
mentioning
confidence: 99%
“…The results showed that 35 cycles of PCR were conducted within 10 min, and three types of human coronavirus (OC43, 229E, and NL63) could be simultaneously detected by distinct fluorescence signals. The fluorescence-based detection showed the potential of our thermal cycler to be utilized for quantitative analysis by coupling with a real-time monitoring setup [ 30 ]. These practical applications can pave the way for their application in various biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in 2021, a research group from Griffith University fabricated a portable LAMP device targeting SARS-CoV-2 based on fluorescence emission ( Figure 6 C) [ 107 ]. According to Sreejith et al, the system (costing USD 100) consists of an “aluminum block embedded with a cartridge heater,” a “single-board computer and camera,” and an LED.…”
Section: A Look Into the Point-of-care Lamp Market: Research And Comm...mentioning
confidence: 99%
“…( C ) Sreejith et al’s portable COVID-19 LAMP device. Reprinted with permission from [ 107 ]. Copyright 2021, Sreejith et al, under Creative Commons 4.0 Attribution License.…”
Section: Figurementioning
confidence: 99%